An Analysis of the Shape and Pattern of Lipa' Sabbe Motif as One of the Buginese Traditional Clothes - Andi Sadapotto; Nurul Faradillah; syahrir L; Ibrahim Manda; Isumarni Isumarni; Lababa Lababa; Nurhaedah Nurhaedah (La Ogi : English Language Journal, 2023)
This study tries to investigate the lipa'sabbe (lip seb) shape, style, and meaning. Researchers carried out their studies at Tosora Village, Majauleng sub-district, kab, one of Sengkang City's first weaving communities. Wajo. This study is a qualitative descriptive one that gives a general summary of the appearance, usage, and significance of the lipa'sabbe (lip seb). The Tosora village community, kec. Majaleng, was seen, interviewed, and documented as part of the study's data gathering procedures. According to the research findings, lipa'sabbe (lip seb) patterns may be categorized into three categories: traditional patterns, semi-traditional patterns, and modern patterns. The Tosora village community, kec. Majaleng, was seen, interviewed, and documented as part of the study's data gathering procedures. According to the research findings, lipa'sabbe (lip seb) patterns may be categorized into three categories: traditional patterns, semi-traditional patterns, and modern patterns